2013
DOI: 10.1080/01496395.2012.733790
|View full text |Cite
|
Sign up to set email alerts
|

Application of Oil/Water Nanoemulsions as a New Alternative to Demulsify Crude Oil

Abstract: Oil-in-water nanoemulsions were developed and evaluated for effectiveness in breaking down crude oil emulsions. The nanoemulsions were prepared using two types of ethoxylated nonionic surfactants: nonylphenol and lauryl ether, at a concentration of 12 wt%, and the solvent xylene as the oil phase, at different concentrations (5, 7, and 10 wt%). The results of the demulsification tests showed that the nanoemulsions developed are a viable alternative to break down petroleum emulsions, with efficiency ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Using high concentrations of inhibitor tends to produce self-associations in the bulk rather than adsorption on asphaltene, reducing their effectiveness [11,12]. More recently, a considerable work has grown up around the use of oil/ water nanoemulsions (NEs) in breaking down asphaltene emulsions [13,14,15]. However, efficient methods of enhancing long-term asphaltene stability with reduced AI amount are still much demanded.…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using high concentrations of inhibitor tends to produce self-associations in the bulk rather than adsorption on asphaltene, reducing their effectiveness [11,12]. More recently, a considerable work has grown up around the use of oil/ water nanoemulsions (NEs) in breaking down asphaltene emulsions [13,14,15]. However, efficient methods of enhancing long-term asphaltene stability with reduced AI amount are still much demanded.…”
Section: -Introductionmentioning
confidence: 99%
“…Even in low concentrations, asphaltene molecules are prone to aggregate and precipitate, causing plugging of pipelines and process equipment such as pumps, heat exchangers, or separator tanks. Chemical treatment using asphaltene inhibitors (AIs) is one of the most common methods to prevent asphaltene precipitation. , However, it has a major problem due to the loss of a large amount of chemicals, resulting in high treatment cost . Using high concentrations of AI tends to produce self-associations from a large number of AI molecules in the bulk rather than adsorption on asphaltene, reducing their effectiveness. , More recently, considerable work has been carried out on the use of oil/water nanoemulsions (NEs) in breaking down asphaltene emulsions. However, efficient methods of enhancing long-term asphaltene stability with reduced AI amount are still much in demand.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, , non-ionic polymeric surfactants based on PEO were used to prepare oil-in-water (O/W) nanoemulsions. The systems showed good separation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has developed oil-in-water (O/W) nanoemulsions with different compositions for application in the pharmaceutical and petroleum sectors. , In the latter sector, we have studied their application as alternatives in the process of separating the water and oil phases. …”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, nanoemulsions were prepared using two types of ethoxylated nonionic surfactants (nonylphenol and lauryl ether) along with the solvent xylene as the oil phase, at different concentrations. The results of the demulsification tests showed that the nanoemulsions developed are a viable alternative to break down petroleum emulsions, with efficiencies ranging from 90 to 95%.…”
Section: Introductionmentioning
confidence: 99%